Application of cellulases from an alkalothermophilic thermomonospora sp in biopolishing of denims - Anish, Ramakrishnan; Rahman, Mohammad Safikur; Rao, Mala (Biotechnology and Bioengineering, 2007)
Use of cellulase for denim washing is a standard eco-friendly technique to achieve desirable appearance and softness for cotton fabrics and denims. But enzymatic washing of denim till date involved acid cellulase (Trichoderma reesei) and neutral cellulase (Humicola isolens) the use of which has a drawback of backstaining of the indigo dye on to the fabric. Though it has been suggested that pH is a major factor in controlling backstaining there are no reports on use of cellulase under alkaline conditions for denim washing. In this study for the first time an alkali stable endoglucanase from alkalothermophilic Thermomonospora sp. (T-EG) has been used for denim biofinishing under alkaline conditions. T-EG is effective in removing hairiness with negligible weight loss and imparting softness to the fabric. Higher abrasive reactivity with lower backstaining was a preferred property for denim biofinishing exhibited by T-EG. The activities were comparable to acid and neutral cellulases that are being regularly used. The enzyme was also effective under non-buffering conditions which is an added advantage for use in textile industry. A probable mechanism of enzymatic finishing of cotton fabric has been represented based on the unique properties of T-EG.
Keywords: alkaline conditions; biopolishing; Cellulase; denim; Thermomonospora sp

Biochemical characterization of a novel beta-1-3, 1-4 glucan 4-glucanohydrolase from thermomonospora sp having a single active site for lichenan and xylan - Anish, Ramakrishnan; Rao, Mala (Biochimie, 2007)
A bifunctional high molecular weight (Mr, 64,500 Da) beta-1-3, 1-4 glucan 4-glucanohydrolase was purified to homogeneity from Thermomonospora sp., exhibiting activity towards lichenan and xylan. A kinetic method was used to analyze the active site that hydrolyzes lichenan and xylan. The experimental data was in agreement with the theoretical values calculated for a single active site. Probing the conformation and microenvironment at active site of the enzyme by fluorescent chemo-affinity label, OPTA resulted in the formation of an isoindole derivative with complete inactivation of the enzyme to hydrolyse both lichenan and xylan confirmed the results of kinetic method. OPTA forms an isoindole derivative by cross-linking the proximal thiol and amino groups. The modification of cysteine and lysine residues by DTNB and TNBS respectively abolished the ability of the enzyme to form an isoindole derivative with OPTA, indicating the participation of cysteine and lysine in the formation of isoindole complex. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: 1-4 glucan 4-glucanohydrolase; beta-1-3; bifunctional; O-phthaialdehyde; single active site; Thermomonospora sp.; Xylanase